Frygtens Logik. Den kolde krig – en ny global historie 1917–1961 - Pharo, Helge (Nordisk Østforum, 2021)
Helge Ø. Pharo, University of Oslo, reviews The Logic of Fear. The Cold War - a New Global History 1917-1961, by Poul Villaume (Gads forlag 2020).